NF-κB Pathways in the Pathogenesis of Multiple Sclerosis and the Therapeutic Implications - Leibowitz, Saskia M.; Yan, Jun (Frontiers in Molecular Neuroscience, 2016)
Nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signalling pathways are involved in cell immune responses, apoptosis and infections. In Multiple Sclerosis (MS), NF-κB pathways are changed, leading to increased levels of NF-κB activation in cells. This may indicate a key role for NF-κB in MS pathogenesis. NF-κB signalling is complex, with many elements involved in its activation and regulation. Interestingly, current MS treatments are found to be directly or indirectly linked to NF-κB pathways and act to adjust the innate and adaptive immune system in patients. In this review, we will first focus on the intricacies of NF-κB signalling, including the activating pathways and regulatory elements. Next, we will theorise about the role of NF-κB in MS pathogenesis, based on current research findings, and discuss some of the associated therapeutic implications. Lastly, we will review four new MS treatments which interrupt NF-κB pathways - fingolimod, teriflunomide, dimethyl fumarate and laquinimod - and explain their mechanisms, and the possible strategy for MS treatments in the future.